International Support for Democracy in Nepal (Department of International Relations, Universitas Brawijaya, 2021)
This study explores the roles of international communities in the democratization process particularly in the post-conflict contexts of Nepal. Based on the main courses of Constituent Assembly Elections of 2008 and 2013 on the background of the civil war (1996 - 2006) and peace process, the analyses of related data showed that international community assisted not only to the peace process through playing different roles such as of a facilitator, a technical supporter, a monitor, a diplomatic good office in the peace process but also as a technical and generous supporter to Election Commission for managing free, fair and credible elections. The support was to the Election Commission, the peace process, to the legislature parliament and all these have made more contributions on institutional and managerial aspects for democracy promotion while equal focus has to be on the people’s level for deliberative democracy.